2022
DOI: 10.1186/s12875-022-01660-8
|View full text |Cite
|
Sign up to set email alerts
|

Let’s talk about sex: exploring factors influencing the discussion of sexual health among chronically Ill patients in general practice

Abstract: Background Chronic diseases are often associated with sexual dysfunction (SD). Little is known about the practice patterns of general practitioners (GPs) regarding sexual care for chronically ill patients. Therefore, the aim of this study was to examine; to what extent GPs discuss SD with chronically ill patients; the barriers that may stop them; and the factors associated with discussing SD. Methods A cross-sectional survey using a 58-item questio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 36 publications
0
4
0
2
Order By: Relevance
“…In fact, if the patients themselves do not spontaneously raise the topic of sexual health, most physicians fail to address it with chronic patients in GP [47]. Furthermore, patients with genitourinary issues may also have to get undressed for clinical examination, which makes them vulnerable, thus requiring greater physician empathy and consideration, which may also explain why PPPE was lower in those patients.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, if the patients themselves do not spontaneously raise the topic of sexual health, most physicians fail to address it with chronic patients in GP [47]. Furthermore, patients with genitourinary issues may also have to get undressed for clinical examination, which makes them vulnerable, thus requiring greater physician empathy and consideration, which may also explain why PPPE was lower in those patients.…”
Section: Discussionmentioning
confidence: 99%
“…However, they seldom asked about possible side effects related to sexual health during follow-up consultations 25 . In a Dutch study 33 of 204 questionnaires completed by general practitioners, 68% of participants never discussed sexual dysfunction with their chronically ill patients during the first consultation, but 54% discussed the issue during a follow-up visit. Two previous studies 34 , 35 among nursing students examined this issue.…”
Section: Discussionmentioning
confidence: 99%
“… 15 , 16 Factors for health professionals failing to identify and manage patients with sexual dysfunction could be time constraints, low awareness of sexual dysfunction, lack of training about diagnostic tools and treatment options, cultural barriers and fear of broaching the topic. 17 , 18 In contrast, up to 91% of patients indicated that they would be comfortable if their health professional raised the issue. 18 In addition, many people with sexual health concerns do not even attempt to seek medical help.…”
Section: Challenges To Sexual Healthcarementioning
confidence: 99%